Use of a cohorting-unit and systematic surveillance cultures to control a Klebsiella pneumoniae carbapenemase (KPC)–producing Enterobacteriaceae outbreak. (14th May 2019) - Reeme, Allison E.; Bowler, Sarah L.; Buchan, Blake W.; Graham, Mary Beth; Behrens, Elizabeth; Singh, Siddhartha; Hong, Johnny C.; Arvan, Jennifer; Hyke, Joshua W.; Palen, Louis; Savage, Sabrina; Seliger, Heather; et al.
Abstract: Objective: Describe the epidemiological and molecular characteristics of an outbreak of Klebsiella pneumoniae carbapenemase (KPC)–producing organisms and the novel use of a cohorting unit for its control. Design: Observational study. Setting: A 566-room academic teaching facility in Milwaukee, Wisconsin. Patients: Solid-organ transplant recipients. Methods: Infection control bundles were used throughout the time of observation. All KPC cases were intermittently housed in a cohorting unit with dedicated nurses and nursing aids. The rooms used in the cohorting unit had anterooms where clean supplies and linens were placed. Spread of KPC-producing organisms was determined using rectal surveillance cultures on admission and weekly thereafter among all consecutive patients admitted to the involved units. KPC-positive strains underwent pulsed-field gel electrophoresis and whole-genome sequencing. Results: A total of 8 KPC cases (5 identified by surveillance) were identified from April 2016 to April 2017. After the index patient, 3 patients acquired KPC-producing organisms despite implementation of an infection control bundle. This prompted the use of a cohorting unit, which immediately halted transmission, and the single remaining KPC case was transferred out of the cohorting unit. However, additional KPC cases were identified within 2 months. Once the cohorting unit was reopened, no additional KPC cases occurred. The KPC-positive species identified during this outbreak included Klebsiella pneumoniae, Enterobacter cloacae complex, and Escherichia coli. bla KPC was identified on at least 2 plasmid backbones. Conclusions: A complex KPC outbreak involving both clonal and plasmid-mediated dissemination was controlled using weekly surveillances and a cohorting unit.